2015
DOI: 10.1177/1545968315606990
|View full text |Cite
|
Sign up to set email alerts
|

Short-Duration and Intensive Training Improves Long-Term Reaching Performance in Individuals With Chronic Stroke

Abstract: Previous studies have shown that multiple sessions of reach training lead to long-term improvements in movement time and smoothness in individuals post-stroke. Yet, such long-term training regimens are often difficult to implement in actual clinical settings. Here, we evaluated the long-term and generalization effects of short-duration and intensive reach training in 16 individuals with chronic stroke and mild to moderate impairments. Participants performed two sessions of unassisted intensive reach training, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 61 publications
(93 reference statements)
1
37
0
Order By: Relevance
“…Finally, as noted the 0 hour group shows significant increase in the MAL during and post-training. In addition to the MAL, each assessment consisted of arm reaching tests comprised with approximately 200 movements with the more affected arm 11 , in addition to the WMFT test (in which subjects perform goal-directed arm and hand movements).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, as noted the 0 hour group shows significant increase in the MAL during and post-training. In addition to the MAL, each assessment consisted of arm reaching tests comprised with approximately 200 movements with the more affected arm 11 , in addition to the WMFT test (in which subjects perform goal-directed arm and hand movements).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies have shown decay of the gains post-training, as least for subgroups of patients 13 , others have shown that the gains can be maintained after training 11,14 , yet others have shown that the gains can even further increase following training, possibly through "self-training" if arm use is sufficient 13,[15][16][17] Here, we analyzed the changes in the Quality of Movement sub-scale of the Motor Activity Log (henceforth, the MAL) in the DOSE trial 9 , in which participants with chronic stroke were randomized into four dose groups. The total doses (0, 15, 30 and 60 hours) were equally distributed over the three bouts of training, as shown in Figure 1B.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, a foremost question is how much of improvement any short‐term intervention could achieve in the late chronic state. Recent reports offer some encouraging findings of motor improvement observed after just one of two training sessions . However, such an explicit improvement is specific for the trained movement, and hard to generalize to other daily actions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports offer some encouraging findings of motor improvement observed after just one of two training sessions. 38,39 However, such an explicit improvement is specific for the trained movement, and hard to generalize to other daily actions. The standard assessment tasks used here were not the focus of repetitive training in either therapy program.…”
Section: Discussionmentioning
confidence: 99%